Comunidad Fitoplanctónica del Río Topo, Tungurahua-Ecuador - Maila, Maria (2017)
The present study is a descriptive one, the same one that was carried out in January 2012. The objective of the study was to determine the phytoplankton component in the riparian zone of Río Topo in the section corresponding to Baños Canton, Río Negro Parish. Four sampling points located in the area of direct influence of the “Hidrotopo” Hydroelectric Project, named: Point 1 “Engine room”, point 2 “Unloading”, point 3 “Before the water intake” and point 4 “After the water intake”. The 128 collection of samples was done by means of stone scraping and filtration. In the laboratory, the 10-mL concentrated sample scanning technique was applied with nine repetitions per point. The samples are in the Laboratory of Microbiology of the Natural and Environmental Sciences, Biology and Chemistry major of Central University of Ecuador. After the analysis, a total of 946 individuals were grouped in 37 genera, 29 families, 19 orders and 5 divisions. The most representative division corresponds to Bacillariophyta, with 424 individuals distributed in 9 orders, 12 families and 15 genera. According to the Shannon-Wiener Diversity Index, the water body is located in the High Diversity category except the “Discharge” point, and a low similarity between the monitored stations is determined via the Sorensen Similarity Índex. When comparing the Topo River with the Pilaló River, it is determined that the number of genera are not dissimilar. Therefore, a total of 42 is recorded in the Pilaló River and a total of 37 in the Topo River. Of the dominant genera, four Genera are common to both bodies of water, and according to Sorensen’s Similarity Index the value is 58%.